Episodic simulation and episodic memory can increase intentions to help others - Gaesser, Brendan (National Academy of Sciences, 2014)
Empathy plays an important role in human social interaction. A multifaceted construct, empathy includes a prosocial motivation or intention to help others in need. Although humans are often willing to help others in need, at times (e.g., during intergroup conflict), empathic responses are diminished or absent. Research examining the cognitive mechanisms underlying prosocial tendencies has focused on the facilitating roles of perspective taking and emotion sharing but has not previously elucidated the contributions of episodic simulation and memory to facilitating prosocial intentions. Here, we investigated whether humans’ ability to construct episodes by vividly imagining (episodic simulation) or remembering (episodic memory) specific events also supports a willingness to help others. Three experiments provide evidence that, when participants were presented with a situation depicting another person’s plight, the act of imagining an event of helping the person or remembering a related past event of helping others increased prosocial intentions to help the present person in need, compared with various control conditions. We also report evidence suggesting that the vividness of constructed episodes—rather than simply heightened emotional reactions or degree of perspective taking—supports this effect. Our results shed light on a role that episodic simulation and memory can play in fostering empathy and begin to offer insight into the underlying mechanisms.